2020
DOI: 10.17269/s41997-020-00427-x
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco and COVID-19: a crisis within a crisis?

Abstract: During the pandemic, the world's media have publicized preliminary findings suggesting that tobacco use is protective against COVID-19. An ad hoc multidisciplinary group was created to address the major public health implications of this messaging. Key messages of this commentary are as follows: 1) The COVID-19 crisis may increase tobacco consumption and decrease access to healthcare. As a result, smoking-related morbidity and mortality could increase in the coming months and years; 2) Smoking and tobacco-rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 31 publications
0
35
0
3
Order By: Relevance
“…While no clear relationship has been established so far between smoking and COVID-19, evidence suggests that tobacco use increases the severity of the disease among COVID-19 patients [ 14 , 16 , 17 ]. During the previous Middle East respiratory syndrome coronavirus (MERS-CoV) outbreak as well, smokers were twice as likely to be affected by and incur deaths from the influenza than non-smokers [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…While no clear relationship has been established so far between smoking and COVID-19, evidence suggests that tobacco use increases the severity of the disease among COVID-19 patients [ 14 , 16 , 17 ]. During the previous Middle East respiratory syndrome coronavirus (MERS-CoV) outbreak as well, smokers were twice as likely to be affected by and incur deaths from the influenza than non-smokers [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…En l’absence d’études cas-témoins appariées, ces données observationnelles doivent être analysées en tenant compte de nombreux biais possibles [8] , [9] , [10] : la qualité du recueil du statut tabagique, volontiers incomplet car souvent issu d’une recherche rétrospective dans les dossiers médicaux, dont on connait le peu de fiabilité [11] et pouvant être faussé en raison du contexte du recueil dans l’urgence ; le manque de données détaillées sur le statut tabagique (données sur le statut d’ex-fumeur souvent absentes ou incomplètes ; études où les sujets sans donnée sur le statut tabagique sont classés comme non-fumeurs), ou pour les ex-fumeurs l’absence d’information sur le délai entre l’arrêt du tabac et la maladie : un fumeur ayant arrêté très récemment est susceptible d’avoir un risque équivalent à celui d’un fumeur et dans ce cas c’est l’impact des statuts fumeur + ex-fumeur qu’il faudrait logiquement analyser. À noter d’ailleurs, qu’indépendamment du statut tabagique, les patients ayant un diagnostic récent de maladie liée au tabac présentent un risque considérablement accru de Covid-19 [12] ; pour certaines études, un manque d’ajustement sur le sexe, l’âge (ajustement fondamental étant donné la répartition particulière de la Covid-19 selon ces deux critères) et de prise en compte d’autres facteurs, notamment les pathologies liées au tabagisme qui peuvent comporter une prévalence moindre de fumeurs, ces patients étant fréquemment devenus abstinents ; le choix le plus souvent inapproprié de la population générale du pays comme population de référence, alors qu’il faudrait choisir une population de sujets hospitalisés, puisque la majorité de ces études concernent des patients hospitalisés ; il est possible également que les fumeurs soient moins susceptibles d’être contaminés, en raison de la réduction de fréquence et de durée de leurs contacts sociaux [13] . quant au sexe-ratio H/F des patients, de l’ordre de 60 % pour la Covid-19, il n’est pas cohérent avec l’hypothèse que fumer serait protecteur, en particulier dans les études réalisées en Chine, pays où le tabagisme est très majoritairement masculin [14] .…”
Section: Est-ce Que Fumer Augmente Ou Diminue Le Risque D’attraper Launclassified
“…il est possible également que les fumeurs soient moins susceptibles d’être contaminés, en raison de la réduction de fréquence et de durée de leurs contacts sociaux [13] .…”
Section: Est-ce Que Fumer Augmente Ou Diminue Le Risque D’attraper Launclassified
“…In addition, the e-cigarette liquid has also been shown to increase inflammation and susceptibility to viral infection in primary human airway cells ( 6 ). Currently, in the midst of the SARS-CoV-2 pandemic, there is renewed interest in the relationship between tobacco products and susceptibility to respiratory viruses, especially those that can cause severe diseases such as influenza viruses and SARS-CoV-2 ( 7 ). Recent findings suggested that e-cigarette usage may also contribute to an increase in susceptibility to viral infection, as it alters the antiviral immune response ( 8 ).…”
mentioning
confidence: 99%